Defeated Heroes: The Representation of Women in the Film Women from Rote Island - Namira Choirani Fajri; Nonny Rulisty Putri Sutikno (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study aims to analyze the representation of women in the film "Women from Rote Island" through Todorov's narrative structure approach. The film depicts the persistent gender injustice experienced by the female characters, never achieving balance. This study uses narrative analysis with Todorov's theory to identify the characters' journeys in the film. Data were collected from scenes and dialogues that represent gender injustice and women's resistance efforts. The analysis was conducted by highlighting how the film depicts a recurring cycle of violence and powerlessness. The results show that the main characters, Bertha, Martha, and Orpah, never manage to escape the cycle of oppression. Bertha, who attempts to seek justice for her sister, ends in a tragic death. Martha becomes another victim of sexual violence, while Orpah is trapped in an oppressive power relationship. The film emphasizes that patriarchal domination not only limits women's freedom of movement but also destroys any resistance they may make. This study concludes that "Women from Rote Island" represents women as defeated heroes. The women's defeat is not due to a lack of courage, but rather to a system that structurally places them in a subordinate position.